2014
DOI: 10.1111/bjd.12630
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in pemphigus vulgaris and pemphigus foliaceus

Abstract: Ethnic group, age at presentation, initial intercellular antibody titre and initial Dsg 3 antibody levels all had a significant impact on prognosis of pemphigus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 23 publications
4
26
2
Order By: Relevance
“…Svecova et al 17 proposed that these alleles may also contribute to disease severity of the more common variant, PV. However, in a previous study, 18 our group did not find any link in HLA DRB1* or DQB1* allele frequency with prognosis for either PV or PF.…”
Section: Discussioncontrasting
confidence: 83%
“…Svecova et al 17 proposed that these alleles may also contribute to disease severity of the more common variant, PV. However, in a previous study, 18 our group did not find any link in HLA DRB1* or DQB1* allele frequency with prognosis for either PV or PF.…”
Section: Discussioncontrasting
confidence: 83%
“…Saha et al . demonstrated that higher antidesmoglein 3 antibody titre at baseline was associated with a longer time to remission in pemphigus vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…These oral lesions require prolonged treatment with immunosuppressants and as a result puts patients at an increased risk of side‐effects . Earlier studies have implicated the role of demographic factors, such as sex and age at onset, and clinical factors, such as timing of initial treatment, site and severity of initial disease, in the prognosis of pemphigus vulgaris . Some studies have also suggested that patients with pemphigus vulgaris who have herpes simplex virus (HSV) in the oral cavity have an increased chance of having a more intractable course of oral disease.…”
mentioning
confidence: 99%
“…While several studies have been undertaken to evaluate the risk factors for disease course, relapses and remissions in patients with pemphigus [ 5 - 8 ], few investigations evaluated the risk factors for overall mortality in patients with PV [ 9 - 12 ] and none for PF as a separate entity.…”
Section: Introductionmentioning
confidence: 99%